Designing and delivering skills transferability and employment mobility: the challenges of a market-driven vocational education and training system - Gekara, Victor [Verfasser]; Snell, Darryn [Verfasser] (My University, 2018)
"As job security declines and precarious employment arrangements become more prevalent, transferable skills have become vital for job seeking success. In recognition of this issue, many governments are seeking to redesign their training systems in ways that transferable skills become better emphasised. This paper examines the challenges of developing transferable skills among a nation’s workforce and the tensions that can emerge between training design intentions and training delivery outcomes when training delivery is marketised. Australia, where incremental training sector reforms have occurred since the late 1980s, serves as the context for this study. While training design occurs through a tripartite process involving employer, government and union representatives, training delivery is now determined in an open, deregulated market environment. Our analysis reveals a complex underlying design with an in-built intention of developing widely transferable skills, yet there exists significant concern about the actual training outcomes. We conclude that in an environment where VET delivery is user-choice driven with the aim of fulfilling specific employer skills needs the quality, depth and breadth of transferable skills are compromised." (Author's abstract, BIBB-Doku)
Keywords: S 2.2.2.1 Ausbildungsordnungen; G 1.3.1.1 Ausbildungsstellenmarkt; I 2.3.5 Australien, Ozeanien; Berufsbildungssystem; Ausbildungsinhalt; Berufsbild; Ausbildungsplatzangebot; Australien